2017
DOI: 10.1111/wre.12264
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation variability and adaptive potential for reduced glyphosate sensitivity in Alopecurus myosuroides

Abstract: SummaryGlyphosate use in the United Kingdom has more than doubled in the last 20 years. Much of this increase is driven by efforts to control herbicide resistant weeds, particularly Alopecurus myosuroides, prior to crop drilling. There is precedent for evolution of glyphosate resistance in similar situations, raising concerns over the sustainability of glyphosate use in the UK. We used dose–response experiments to examine variation in glyphosate sensitivity amongst 40 field‐collected A. myosuroides populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Glyphosate resistant weeds are already found on almost every continent 20 but are not yet present in the UK. However, English farmers are increasingly reliant on glyphosate to control herbicideresistant black-grass and as a result there has been a dramatic increase in its use 42 , ramping 30 . In the US, widespread glyphosate resistance is already a reality and the scale of the problem dwarfs that being faced with black-grass in England.…”
Section: Discussionmentioning
confidence: 99%
“…Glyphosate resistant weeds are already found on almost every continent 20 but are not yet present in the UK. However, English farmers are increasingly reliant on glyphosate to control herbicideresistant black-grass and as a result there has been a dramatic increase in its use 42 , ramping 30 . In the US, widespread glyphosate resistance is already a reality and the scale of the problem dwarfs that being faced with black-grass in England.…”
Section: Discussionmentioning
confidence: 99%
“…The recent appearance of glyphosate‐resistant populations of A. palmeri in Brazil with EPSPS gene duplication hints at the potential for intercontinental spread of resistance mutations, mediated by seed movement (Küpper et al ., ). Experiments have demonstrated that glyphosate‐sensitive populations of L. rigidum (Busi & Powles, ) and Alopecurus myosuroides (Davies & Neve, ) harbor heritable standing variation for glyphosate insensitivity, although this additive genetic variation may be distinct from the mechanisms of resistance selected in field‐evolved resistant weed populations. Selection for glyphosate resistance and susceptibility in diverse lines of Ipomoea purpurea also demonstrated heritable standing genetic variation for glyphosate insensitivity (Debban et al ., ).…”
Section: Evolutionary Dynamics Of a ‘Rare’ Resistance Traitmentioning
confidence: 99%
“…The reduced sensitivity of the suspected resistant populations was greater than reported in a number of previous studies that have identified significant variation in glyphosate response in sensitive weed populations. Davies and Neve (2017) reported ED 90 values in UK blackgrass (Alopecurus myosuroides Huds.) ranging from 354 to 610 g ha − 1 .…”
Section: Weed Science 45mentioning
confidence: 99%